Crystallographic ordering of Al and Sn in α-Ti. (15th March 2023) - Worsnop, Felicity F.; Lea, Susannah L.M.; Ilavsky, Jan; Rugg, David; Dye, David
Abstract: Increasing attention is being paid to α 2 Ti3 (Al, Sn) precipitation from the α phase of titanium alloys owing to its effect on slip band formation, localisation and the implications for fatigue performance in jet engine titanium. However, the early stages of α 2 precipitation have historically been difficult to observe by electron microscopy, neutron diffraction or atom probe analysis. Here, small angle X-ray scattering is used to reexamine the phase boundary in binary Ti-Al and Ti-Sn alloys with around 500 ppmw O. It is found that the phase boundaries in the literature are approximately correct, at 6.2 wt.% Al and 16.9 wt.% Sn, and that this favours the use of Al as a solid solution strengthener over Sn for ambient temperature applications. However, once O content and phase partitioning in α+β alloys are taken into account, this implies that Aleq limits for future alloy design of critical rotating parts should be lowered substantially. Graphical abstract: